2018
DOI: 10.3989/gya.1098171
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and structural variations in hazelnut and soybean oils after ozone treatments

Abstract: SUMMARY:In the present work, the effect of ozone treatments on the structural properties of soybean oil (SBO) and hazelnut oil (HO) were investigated. The study presents the findings and results about the oxidation of HO and SBO with ozone, which has not been fully studied previously. The HO and SBO were treated with ozone gas for 1, 5, 15, 30, 60, 180 and 360 min. The ozone reactivity with the SBO and HO during the ozone treatment was analyzed by 1 H, 13 C NMR, FTIR and GC. The iodine value, viscosity and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
4
5
0
Order By: Relevance
“…In general, the content of identified unsaturated fatty acid in oil decreased with the increase of ozonation time and, consequently, the peroxide value increased. On the contrary, almost all saturated fatty acids, except C20:0, increased significantly with the time of ozonation, reaching its highest value in sample 6 (360 min of ozonation), which is consistent with other studies, because oxidation causes the increase in relative percentages of saturated fatty acids and a decrease of relative percentages of unsaturated fatty acids [32,33]. All unsaturated fatty acids, except the α-linolenic acid (C18:3n3), were detected in all samples, which indicates that ozone did not react with all double bonds of these acids, which remained as modified triglycerides and non-modified triglycerides, and can then be oxidized by the oxygenated compounds formed [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, the content of identified unsaturated fatty acid in oil decreased with the increase of ozonation time and, consequently, the peroxide value increased. On the contrary, almost all saturated fatty acids, except C20:0, increased significantly with the time of ozonation, reaching its highest value in sample 6 (360 min of ozonation), which is consistent with other studies, because oxidation causes the increase in relative percentages of saturated fatty acids and a decrease of relative percentages of unsaturated fatty acids [32,33]. All unsaturated fatty acids, except the α-linolenic acid (C18:3n3), were detected in all samples, which indicates that ozone did not react with all double bonds of these acids, which remained as modified triglycerides and non-modified triglycerides, and can then be oxidized by the oxygenated compounds formed [31].…”
Section: Discussionsupporting
confidence: 92%
“…All unsaturated fatty acids, except the α-linolenic acid (C18:3n3), were detected in all samples, which indicates that ozone did not react with all double bonds of these acids, which remained as modified triglycerides and non-modified triglycerides, and can then be oxidized by the oxygenated compounds formed [31]. The percentages of identified unsaturated fatty acids in samples 5 and 6 (160 and 320 min of treatment) decreased rapidly, which is in accordance with the results obtained in other studies, leading to a decrease in the percentages of oleic and linoleic acids [32,34]. The oxidation of oleic acid comprises the break of the carbon-carbon double bond at position nine of the carbon backbone [35].…”
Section: Discussionsupporting
confidence: 90%
“…The significant decline in the content of α-tocopherol in oil was noted after 10 and 20 ppm, especially 20 min of ozonation. It was agreed that previously studied, the tocopherol content of hazelnut samples has decreased with storage time (Enami et al, 2009;Uzun et al, 2018).…”
Section: F I G U R Esupporting
confidence: 89%
“…() have suggested that α‐tocopherol does not react directly with ozone in biological systems, but is consumed instead by free radical reactions secondary to ozonation. The FTIR analysis (Uzun et al ., ) confirmed that the intensity and frequency of the bands related to the carbon‐carbon double bonds decreased or these bands became overlapping and broadened as ozone treatment time was extended. In our studies we observed the same dependence.…”
Section: Resultsmentioning
confidence: 60%